Pengaruh Kecerdasan Intelektual dan Kecerdasan Spiritual terhadap Kinerja Karyawan: Survei pada Karyawan Non Manajer pada Hotel Grand Metro Tasikmalaya - Syahril Ramdani; Arga Sutrisna; Barin Barlian (CV. Ulil Albab Corp, 2022)
This study aims to examine and analyze the effect of Intellectual Intelligence and Spiritual Intelligence on the Performance of Non Managers at Hotel Grand Metro Tasikmalaya. Respondents in this study were non-manager employees at the Grand Metro Tasikmalaya Hotel. Based on the sample method, the number of samples in the study was 34 respondents. In this study using primary data obtained from the distribution of questionnaires. The number of questionnaires distributed was 34 and 34 employees that could be returned and processed. The analytical method used in this research is multiple linear analysis. The results showed that intellectual intelligence had a significant effect on employee performance, spiritual intelligence had a significant effect on employee performance and spiritual intelligence simultaneously had a positive and significant effect on employee performance. This means that when intellectual intelligence and spiritual intelligence increase employee performance.